(untitled) (Sains Humanika, 2024)
Learning engagement is a crucial aspect of educational success, yet its complexities remain a subject of ongoing investigation. This systematic literature review presents a comprehensive synthesis of empirical research on learning engagement, meticulously curated through a thorough review process. Drawing upon a diverse array of scholarly works, this review delves into the antecedents and outcomes of learning engagement, shedding light on its multifaceted nature. Various measurement methods, including surveys, interviews, and observation, are explored, emphasizing the diverse approaches to understanding and assessing engagement. Key findings underscore the pivotal roles of intrinsic motivation, perceived value, self-regulation, and social support in nurturing learning engagement among learners. Moreover, methodological considerations are critically examined, paving the way for future research avenues aimed at deepening our comprehension of learning engagement dynamics within diverse educational contexts. This review serves as a valuable resource for educators, researchers, and policymakers seeking to enhance student engagement and academic outcomes.